Results on life cycle assessments to determine impacts of agronomic management choices in the Cauca and Honduras CSV - Loaiza, Sandra; Chirinda, Ngonidzashe; Martínez Barón, Deissy; Martínez, Jesús David (2019)
The intense management of the crops, that characterizes current agricultural cropping systems, has resulted in increased concentrations of greenhouse gases (GHGs) such as carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O). In this study, we used the field-scale agricultural assessment model - Cool Farm Tool (CFT), to model GHG emissions and uptake estimates (Hillier et al., 2011). This tool combines different algorithms that integrate climate, soil and crop data and presents outputs on carbon footprints in a format that is accessible to non-experts. Furthermore, the CFT provides the possibility to compare GHG emissions and uptake estimates from different production sites and systems. Finally, the tool CFT enables crop producers and stakeholders to take a more informed and holistic approach to environmental sustainability in the agricultural sector.